Cancer predisposition syndromes: Lessons for truly precision medicine - Church, D (Wiley, 2017)
Cancer predisposition syndromes are typically uncommon, monogenic, high-penetrance disorders. Despite their rarity, they have proven to be highly clinically relevant in directing cancer prevention strategies. As such, they are similar to an expanding class of low-frequency somatic mutations that are associated with a striking prognostic or predictive effect in the tumours in which they occur. This talk aims to highlight these commonalities, with particular reference to mutations in the proofreading domain of replicative DNA polymerases – the focus of work in my laboratory during the last few years.